Role Of Plant-Based Bioflavonoids in Combating Tuberculosis - Vijaya, S.; Admuthe, Namdeo Bhagwan; Sreenivas, A; Garg, Har Govind; Malar, S. Ezhil; S, Vinayaka K.; Padghane, Sharda Natthu; Shrivastava, Ruchita; Barwant, Mukul Machhindra (International Journal of Membrane Science and Technology, 2023)
Innovative strategies are required to address the ongoing threat of tuberculosis (TB), which continues to be a serious worldwide health issue. Growing interest has been paid to plant-based bioflavonoids because of their potential as TB adjunctive treatments. This chapter offers a thorough examination of the varied function of bioflavonoids in TB treatment. The first sections highlight bioflavonoids' natural defense roles in plants while describing their chemical diversity and origins. We study the mechanisms of action of bioflavonoids on Mycobacterium TB, including how they interfere with biofilm development, virulence factors, and host immunological responses. Notably, the potential for decreased drug resistance and shortened treatment durations is highlighted when discussing the synergistic effects between bioflavonoids and traditional TB medications. The anti-inflammatory properties of bioflavonoids are examined in the context of TB pathogenesis, addressing their role in modulating inflammatory responses and mitigating tissue damage. Clinical studies evaluating bioflavonoid efficacy, safety, and bioavailability are reviewed, providing insights into their therapeutic potential. Challenges associated with bioavailability and formulation are also discussed, highlighting strategies to optimize drug delivery.Incorporating ethnobotanical perspectives, we explore historical plant-based remedies for TB and the integration of traditional knowledge with modern research. The abstract concludes by outlining future directions, emphasizing promising bioflavonoid candidates for TB treatment, targeting latent infections, and advocating for collaborative, interdisciplinary research efforts. Ultimately, this chapter underscores the promising role of plant-based bioflavonoids as a potential avenue for enhancing the efficacy and resilience of TB treatment strategies, offering hope for improved outcomes in TB management.